REPRESENTACIÓN FEMENINA LEGISLATIVA Y MUNICIPAL EN EL 2002. EL VALOR DE LAS CUOTAS Y LA TRAMPA DE LAS VICEALCALDÍAS - Blanco Lizano, Randall (Universidad de Costa Rica, 2005)
The article establishes a series of social and political tendencies presents in the Costa Rican society of the last two decades that affect the electoral behavior of citizens. Thehappened main changes in the national elections of the 2002 are analyzed and establishes a comparison between the results of the feminine participation in the legislative and local level (by province) to illustrate the unequal effects of the application of the mechanism of the minimum quotas of feminine representation in the different political levels.